Divine Attributes in the Book of Joel - Watson, Douglas (Journal for the study of the Old Testament, 2012)
Disagreement about the substance of the book of Joel is due, in part, to the complexity of and inconsistency in the book's portrait of the deity. This article seeks to unpack four divine attributes that undergird the complicated presentation of Yhwh in the book of Joel's interpretation of disaster: divine abandonment, divine aggression, divine compassion, and divine judgment. In each case, the portrait of the deity that emerges is rooted in the literature of Israelite laments. The importance of Israelite laments in shaping the themes, motifs, and metaphors of the book of Joel offers clues about the religious tradition from which the text emerged.